Prolene plug repair for femoral hernia. - Allan, S. M. (Royal College of Surgeons of England, 1989)
We present the technique and our results in using a plug of Prolene mesh to repair femoral hernias. By filling the femoral canal with a Prolene plug we achieved a sound hernia repair. Our results allow us to recommend the technique to others.